Applying Plant Hydraulic Physiology Methods to Investigate Desiccation During Prolonged Cold Storage of Horticultural Trees - Sheridan, Rebecca A.; Nackley, Lloyd L. (Frontiers in Plant Science, 2022)
Plant nursery production systems are a multi-billion-dollar, international, horticultural industry that depends on storing and shipping live plants. The storage environment represents potentially desiccating conditions for dormant, bareroot, deciduous horticulture crops, like orchard trees, forestry trees, ornamental trees, and grapevines. The plant hydraulics framework posits that plants experiencing water stress ultimately die from hydraulic failure or carbon starvation. We hypothesized that the plant hydraulics framework can be applied to stored crops to determine if hydraulic failure or carbon starvation could be attributed to mortality. We used deciduous trees as model species because they are important horticultural crops and provide a diversity of hydraulic strategies. We selected cultivars from six genera: Acer, Amelanchier, Gleditsia, Gymnocladus, Malus, and Quercus. For each cultivar, we measured stem hydraulic conductance and vulnerability to embolism. Over 14 weeks (March - June), we removed trees of each cultivar (n = 7) from cold storage (1-2 oC) and measured stem water potential, water content, each week. At three times during this period we also measured nonstructural carbohydrates. Each week, we planted trees from each cultivar (n = 10) to track survival and growth. Our results showed that for four cultivars (Acer, Amelanchier, Malus, and Quercus) the stem water potentials measured in trees removed from storage did not exceed stem P50, the water potential at which 50% of stem hydraulic conductivity is lost. This suggests that the water transport system remains intact during storage. For two cultivars (Gleditsia and Gymnocladus) the water potential measured on trees out of storage exceeded stem P50, yet planted trees from all weeks survived and grew. In the 14 weeks, there were no significant changes or directional trends in stem water potential, water content, or NSC for most cultivars, with a few exceptions. Overall, the results show that the trees did not experience detrimental water relations or carbon starvation thresholds. Our results suggest that many young deciduous trees are resilient to conditions caused by prolonged dormancy and validate the current storage methods. This experiment provides an example of how a mechanistically-based understanding of physiological responses can inform cold storage regimes in nursery tree production.